Optimization of Hypercholesterolemia Treatment after Heart Transplant: The Role of PCSK9 Inhibitors - Valero-Masa, María Jesús; Ortiz-Bautista, Carlos David; Castrodeza, Javier; Martínez-Sellés, Manuel (Current Pharmaceutical Design, 2024)
BackgroundPrevious studies have reported the benefit of statins after heart transplant (HT). However, the use of high-dose statins might be limited in some HT patients due to intolerance and interactions with immunosuppression or might not be enough to achieve low-density lipoprotein (LDL) cholesterol goals. Hyperlipidemia has been associated with coronary allograft vasculopathy. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors might be a safe and effective option in HT patients with suboptimal lipid control.MethodsIn a retrospective study, we identified HT patients in our center with LDL cholesterol >100 mg/dL, after diet modifications and up-titration of statins to maximum tolerated dose, treated with PCSK9i. The primary endpoint was LDL reduction one month after, and secondary endpoints were the development of donor-specific HLA antibodies (DSA) and the presence of coronary allograft vasculopathy or rejection.ResultsFrom January, 2018, to January, 2024, we identified five HT patients treated with PCSK9 inhibitors. In all cases, evolocumab was used. A significant reduction in LDL cholesterol was observed (151.6 ± 13.5 mg/dl to 72.4 ± 14.6 mg/dl; p = 0.04, mean reduction 75.7 ± 14.1 mg/dl), as well as in total cholesterol (231 ± 34.6 mg/dl to 152.2 ± 38.9 mg/dl; p < 0.01, mean reduction 78.8 ± 22.2 mg/dl). A significant increase in HDL cholesterol was not observed (45.4 ± 10.9 mg/dl to 46.2 ± 11.1 mg/dl; p = 0.60). One patient developed DSA five years after treatment onset. Rejection and coronary allograft vasculopathy were not observed.ConclusionPCSK9 inhibitors are safe and effective in reducing LDL in HT patients. However, larger studies are needed to clarify if they can reduce the development of coronary allograft vasculopathy.
Keywords: Heart transplant